Rupture of a detachable-tip microcatheter away from the detachment zone during Onyx 18 embolization of an arteriovenous malformation and management of the complication. (24th January 2022) - Cortese, Jonathan; Coskun, Oguzhan; Di Maria, Federico; Pizzuto, Silvia; Rodesch, Georges; Consoli, Arturo
Abstract : Leakage of liquid embolic material is a rare but dreaded complication during embolization of an arteriovenous malformation (AVM). We describe the rupture of a microcatheter away from the detachment site and the successful removal of the cast of Onyx 18 in the carotid artery by aspiration. A young adult patient diagnosed with a right temporal unruptured AVM underwent endovascular embolization using Onyx 18. The AVM was approached using an Apollo microcatheter. After 4 min of Onyx 18 injection, leakage of Onyx 18 in the petrous segment of the internal carotid artery was noticed while the distal tip of the microcatheter remained patent. The plug of Onyx was successfully removed using an aspiration technique via the Envoy DA catheter. Analysis of the microcatheter confirmed that the rupture occurred away from the detachment site. However, no definite cause for the rupture has been identified.